PENGARUH PENGALAMAN MENJUAL, KOMPETENSI MENJUAL DAN KUALITAS HUBUNGAN UNTUK MENINGKATKAN KINERJA TENAGA PENJUALAN (Studi Pada Tenaga Penjualan Smartphone Kota Semarang) - Simarmata, Ester Hilery; Mudiantono, Mudiantono (Diponegoro Journal of Management, 2018)
This study aims to analyze the influence of factors of salesperson’s performance  of smartphone salesperson in Semarang. Selling experience as independent variable and salesperson’s performance as dependent variable. This research uses selling competence and quality of relationship as intervening variables. Sample of this research is the salespersons of smartphone who have been working in Semarang at least 2 months. The sampling method in this research is purposive sampling. The analysis technique used is Structural Equation Modeling –by using AMOS 22.0 analysis tool.             The results of this study show selling experience and selling competence have positive and significant effects on quality of relationship, the selling experience has a positive and significant effect on the selling competence, selling experience and selling competence have positive and significant effects on salesperson’s performance, and quality of relationship has a positive and significant effect on salesperson’s performance.